William Shakespeare's The taming of the shrew [videorecording (DVD)] - Zeffirelli, Franco; Burton, Richard, 1925-1984; Taylor, Elizabeth, 1932-2011; Cusack, Cyril, 1910-1993; Hordern, Michael, 1911-1995; York, Michael, 1942-; Shakespeare, William, 1564-1616 (Columbia TriStar Home Video, 1999)
Petruchio is a poverty-stricken gentleman from Verona who journeys to Padua in search of a wealthy wife. There he meets Katharina, a self-willed shrew who leads Petruchio on a merry chase before he successfully circumvents her attempts to avoid marriage. After the honeymoon, Kate helps Petruchio win a wager that he has the most obedient wife. In reality, Kate has found a more effective way to dominate her mate.